Acreditación de la calidad y sus retos a la gestión - Alvarado Oyarce, Otoniel (2011)
From an operative view, all concerns in this research about the results of the self-evaluation, the externa! evaluation, and the quality improvement are the result of management and maintaining this after being certified (accredited) the institution will also be the consequence ofthe management mechanisms to adopt.One of the possible strategies to cope the educational crisis, in non developed countries, is implementing evaluation programs (specifically self-evaluation) to the consequent accreditation of the educational qua lit y. In this way, the universities of our country, in a more emphatic way than other educational institutions, are experimenting the self-evaluation, to the respective accreditation, waiting that those processes could improve their quality levels and be competitive in globa li zat ion. As usual in our country and very different from others, we have started very late with these processes when in other regions this has been done from the last decade.However, it is not late to formulate sorne ideas, from other views to enable a great comprehension, best application and result of process in the making, in this case ideas about educational management problems resulting from the process.